2001
DOI: 10.1080/003655201317097218
|View full text |Cite
|
Sign up to set email alerts
|

Regular-dose versus High-dose Omeprazole in Peptic Ulcer Bleeding A Prospective Randomized Double-blind Study

Abstract: Under the defined tolerance limits, the regular dose of omeprazole is as successful as a high dose in preventing peptic ulcer rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In preview of such repositioning approach, many recent preclinical and clinical evaluations have highlighted diverse effects of omeprazole other than its proton pump inhibitory actions. Omeprazole is a proton pump inhibitor that is widely used in the treatment of peptic ulcer 7 . In vitro and and in vivo evaluations have proved omeprazole have carbonic anhydrase inhibitory 8 , anti-inflammatory 9 and antioxidant 10 activities.…”
mentioning
confidence: 99%
“…In preview of such repositioning approach, many recent preclinical and clinical evaluations have highlighted diverse effects of omeprazole other than its proton pump inhibitory actions. Omeprazole is a proton pump inhibitor that is widely used in the treatment of peptic ulcer 7 . In vitro and and in vivo evaluations have proved omeprazole have carbonic anhydrase inhibitory 8 , anti-inflammatory 9 and antioxidant 10 activities.…”
mentioning
confidence: 99%
“…Many Western reports have defined that continuous PPI therapy is effective in the prognosis of non-variceal upper gastrointestinal bleeding patients [7]. However, some other European studies reported that there is no statistical significance between intravenous 20 mg once daily omeprazole and continuous infusion of an 80-mg bolus followed by 8 mg/h [12]. In Indian and Iranian studies, oral omeprazole alone 80 mg/day was able to reduce rebleeding rates [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…While in the methods of pantoprazole, there is not any specific dose being established, many studies and trials suggested 80 mg single dose after 40 mg/h for patients with peptic ulcer disease in Asia. [ 32 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to other studies, the efficacy of pantoprazole in the Asian patients is more than Western ones. [ 32 33 ] In addition, pH of the stomach was not measured; hence, it cannot be concluded that both methods are identical in reducing and controlling acid. However, it should be noted that whether both methods have any effect on acid control, it does not change the conclusion of the investigation because the effect of the drug was being investigated.…”
Section: Discussionmentioning
confidence: 99%